Proposi????o de um projeto para inser????o de pequenas empresas nas m??dias sociais - Souza, Rodrigo Menezes de (2019)
The studies about small companies have always been prominent in the academy because of the importance that this kind of organization brings to the economy of the countries and for job???s generation. Because the popularization of social medias such as Facebook, Instagram, Twitter and others, these organizations have sought to insert themselves into these channels in search of greater contact with their consumers and reach previously untapped markets due to geographical limitation in the offline universe. From this phenomenon, academic studies have been trying to explain the causes of this kind of organization to use social media and how they can do to enable actions of insertion in these channels. Such studies are in the early stages and still do not have a clear consensus on ways of using social media especially in the small business universe. The present work aims to address this gap presented as the project management appropriate to the context of small companies can contribute to the process of insertion of these organizations into the social media in a structured way and able to meet the motivators and strategic objectives of the entrepreneurs. For this, a qualitative research was conducted with the Design Science Research method, which developed and validated an artifact for including small companies into social media. At the stage of discovery the problems to be solved by the research, interviews were conducted with three small Brazilian companies with a presence in social media and with business strategies focused on the digital world. In order to build the artifact, bibliometric co-citation and lexical analyzes were performed and for the validation of the artifact a Mann-Whitney statistical analysis of the social media posts carried out by the three companies and response actions of their followers, also new interviews with the entrepreneurs were conducted. As a result, an artifact was presented with motivators focused on innovation, market growth and revenue and the definition that a project for social media in small companies should consider advertising and call to action focused at the product.